Performance Improvement of an Air Cooled Air Conditioning System Using an Evaporative Cooled Condenser - A. Ahmed, Khalid; E. E. Mohamed, Omer (University of Khartoum Engineering Journal, 2022)
The aim of this paper is to investigate the performance improvement of an air-cooled air conditioning system utilizing an evaporative cooled condenser. Air-cooled condensers in many refrigeration and air conditioning systems when used in hot climate are less efficient and have technical, economical, and environmental constraints. As an alternative, the use of evaporative air-cooled condensers, seem to be a unique option to mitigate the limitations above and improve the energy performance of such systems. Another advantage of using evaporative air-cooled condensers is to protect the compressor and keep the system working without interruptions at high outdoor temperatures.To characterize this energy benefit, a model was developed and applied to predict the performance of a variable refrigerant flow (VRF) system under various ambient air temperatures up to 42 °C using an engineering equation solver (EES) software. The results show that the application of the evaporative precooled air in an air-cooled condenser has significant effect on the performance improvement of the air conditioning system. In Khartoum’s hot and dry climate, the rate of improvement is increased as ambient air temperature increases. It is also found that, compared to an air-cooled condensers system, the refrigerant effect and the coefficient of performance of evaporative cooled condensers could be increased by 23% and 60%, respectively. In addition, the compressor work is decreased by 35% followed by a considerable reduction of the operational costs of the system.